Imagination as the Reconstruction of Experience in Katherine Paterson’s Bridge to Terabithia - Dahlan (Universitas Islam Negeri Palopo, 2026)
This study explores the role of imagination as a reconstruction of experience in the novel Bridge to Terabithia by Katherine Paterson through the theoretical lens of Lev Vygotsky. Vygotsky’s concept of imagination emphasizes that creative thought is not separate from reality but is instead formed through the reorganization of lived experiences. This research aims to analyze how the main characters, Jess Aarons and Leslie Burke, construct the imaginary world of Terabithia as a reflection and transformation of their real-life situations, emotions, and social interactions. The study employs a qualitative descriptive method, focusing on textual analysis of key narrative elements, including character development, setting, and dialogue. The findings reveal that Terabithia functions as a symbolic space where the characters process personal struggles such as family pressure, social isolation, and emotional vulnerability. Through imaginative play, the characters reconstruct their experiences into meaningful narratives that support their psychological and emotional growth. Furthermore, the study highlights the importance of social interaction in shaping imagination, as seen in the collaborative creation of Terabithia. This aligns with Vygotsky’s view that imagination develops within a social and cultural context. The novel demonstrates that imagination serves not only as an escape from reality but also as a cognitive and emotional tool for understanding and coping with life experiences